The influence of patent assertion entities on inventor behavior. (15th February 2022) - Chari, Mukund; Steensma, H. Kevin; Connaughton, Charles; Heidl, Ralph
Abstract: Research summary: Patent assertion entities (PAEs) are intermediaries that acquire patents from inventors and license them to firms that use the intellectual property to develop products. We consider how PAE intermediation influences inventor behavior by reducing the costs to monetize their inventions. Using a proprietary dataset that tracks PAE lawsuits, we find that, as PAE intermediation for a given class of technologies increases, larger numbers of focused inventors (i.e., small firms, universities, and labs) that typically lack commercializing capabilities begin to produce inventions in this class. Further, we find that, compared to their larger counterparts, focused inventors are particularly responsive to increasing PAE intermediation by producing greater numbers of inventions, albeit inventions that likely advance the state of the art only incrementally. Managerial summary: Patent assertion entities (PAEs) serve as brokers of intellectual property by purchasing patents from inventors and licensing these patents to firms that develop products based on them. We investigate how PAE brokerage activities influence inventors. We find that as PAEs become more active in a particular class of patents, inventors who lack commercialization capabilities (e.g., small firms, universities, and research labs) are particularly prone to both begin patenting and increase their rate of producing patented inventions in this patent class. We also find, however, that as PAEs become more active in a given patent class, patented inventions produced by inventors lacking commercialization capabilities are increasingly incremental in nature as compared to patented inventions produced by larger firms that commercialize products.